Metabolic load in dairy cows kept in herbage‐based feeding systems and suitability of potential markers for compromised well‐being. Issue 4 (9th March 2016) - Zbinden, R. S.; Falk, M.; Münger, A.; Dohme‐Meier, F.; van Dorland, H. A.; Bruckmaier, R. M.; Gross, J. J.
Summary: Herbage feeding with only little input of concentrates plays an important role in milk production in grassland dominated countries like Switzerland. The objective was to investigate the effects of a solely herbage‐based diet and level of milk production on performance, and variables related to the metabolic, endocrine and inflammatory status to estimate the stress imposed on dairy cows. Twenty‐five multiparous Holstein cows were divided into a control (C+, n  =   13) and a treatment group (C−, n  =   12), according to their previous lactation yield (4679–10 808 kg) from week 3 ante partum until week 8 post‐partum (p.p.). While C+ received fresh herbage plus additional concentrate, no concentrate was fed to C− throughout the experiment. Within C+ and C−, the median of the preceding lactation yields (7752 kg) was used to split cows into a high (HYC+, HYC−)‐ and low‐yielding (LYC+, LYC−) groups. Throughout the study, HYC+ had a higher milk yield (35.9 kg/d) compared to the other subgroups (27.2–31.7 kg/d, p < 0.05). Plasma glucose (3.51 vs. 3.72 mmol/l) and IGF‐1 (66.0 vs. 78.9ng/mL) concentrations were lower in HYC−/LYC− compared to HYC+/LYC+ cows (p < 0.05). Plasma FFA and BHBA concentrations were dramatically elevated in HYC− (1.1 and 1.6 mmol/l) compared to all other subgroups (mean values: 0.5 and 0.6 mmol/l, p < 0.05). Saliva cortisol, plasma concentrations of serum amyloid A (SAA), haptoglobin (Hp), beta‐endorphin (BE) and activity of alkaline phosphatase (AP) were not different between C+ and C−. In conclusion, herbage‐fed high‐yielding cows without supplementary concentrate experienced a high metabolic load resulting in a reduced performance compared to cows of similar potential fed accordingly. Low‐yielding cows performed well without concentrate supplementation. Interestingly, the selected markers for inflammation and stress such as cortisol, Hp, SAA, BE and AP gave no indication for the metabolic load being translated into compromised well‐being.